In celebration of K.C. Hines - McKellar, Bruce H. J.; Amos, Ken; Hines, K. C. (Kenneth Charles), 1926-2005 (World Scientific Pub. Co., 2010)
This book presents a comprehensive review of a diverse range of subjects in physics written by physicists who have all been taught by or are associated with K C Hines. Ken Hines was a great mentor with far-reaching influence on his students who later went on to make outstanding contributions to physics in their careers. The papers provide significant insights into statistical physics, plasma physics from fluorescent lighting to quantum pair plasmas, cosmic ray physics, nuclear reactions, and many other fields.